Fostering Student Learning: EFL Teachers’ Pedagogical Competence and Subject Content on Students’ Achievement - Bachtiar Bachtiar (Journal of ELT, Linguistics, and Literature, 2016)
This study explored whether and how EFL teachers’ pedagogical competence and subject content contribute to gain in students' English achievement. Using correlational study, the results indicated that students’ attitude to teachers’ pedagogical competence and English lesson content were positive. Interestingly, the students’ attitude towards English teachers’ pedagogical competence is higher than the students’ attitude towards English lesson contents. This finding provides support for policy initiatives designed to improve students' English language achievement by increasing EFL teachers’ knowledge and English lesson contents